STUDI PENGARUH VARIASI KOMPOSISI BIORESIN EPOKSI- MINYAK KELAPA SAWIT UNTUK APLIKASI CORE SANDWICH MATERIAL LAMBUNG KAPAL - Novita Sari, Eli; M Fauzi Soulton; Duratun Nasiqiati Rosady, Siti; Kusnandar (Jurnal Inovasi Teknologi Manufaktur, Energi dan Otomotif, 2022)
Vegetable oil is biodegradable, non-toxic, environmentally friendly, and renewable so that it becomes an alternative to replace mineral oil and chemicals. This research will develop a bioresin which is a mixture of epoxy with natural polymer such as palm oil. The homogenization method uses a hot plate so that the mixing reaches miscible materials. The results of bioresin testing with variations in the composition of palm oil showed that the optimal composition variation was E-MS (10%) because it had a low tensile strength value of 53.111Mpa. While the highest elongation value is 14.04767%, and has a low hardness value of 86.3 on the shore D scale. The highest density value is 1.25254(g/cm3). Judging from the standard L’loyd Register and BKI (Indonesian Classification Agency) that the values ​​of all tensile strength test results meet the standards and all variations in the composition of the test results and elongation values ​​meet the minimum criteria.